2016
DOI: 10.1136/gutjnl-2016-311622
|View full text |Cite
|
Sign up to set email alerts
|

Germline variation in inflammation-related pathways and risk of Barrett's oesophagus and oesophageal adenocarcinoma

Abstract: Esophageal adenocarcinoma (EA) incidence has risen sharply in Western countries over recent decades. Local and systemic inflammation, operating downstream of disease-associated exposures, is considered an important contributor to EA pathogenesis. Several risk factors have been identified for EA and its precursor, Barrett’s esophagus (BE), including symptomatic reflux, obesity, and smoking. The role of inherited genetic susceptibility remains an area of active investigation. To explore whether germline variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 54 publications
1
36
0
Order By: Relevance
“…Variants in the cyclooxygenase (COX) pathway were significantly associated with risk of BE. Gene-level analyses identified an association with MGST1 (on chromosome 12p12), and a meta-analysis, which added BE and control participants from the Wellcome Trust GWAS, confirmed associations between 4 SNPs and risk of BE (Figure 2, Supplementary Table 2) 60 . Analyses of GWAS data examining the role of germline variation in other pathways, including the biogenesis and activity of microRNAs 61 , androgens 62 , and the estrogen and oxytocin pathways 63 , also indicated associations, but these have not been replicated.…”
Section: After Gwasmentioning
confidence: 77%
“…Variants in the cyclooxygenase (COX) pathway were significantly associated with risk of BE. Gene-level analyses identified an association with MGST1 (on chromosome 12p12), and a meta-analysis, which added BE and control participants from the Wellcome Trust GWAS, confirmed associations between 4 SNPs and risk of BE (Figure 2, Supplementary Table 2) 60 . Analyses of GWAS data examining the role of germline variation in other pathways, including the biogenesis and activity of microRNAs 61 , androgens 62 , and the estrogen and oxytocin pathways 63 , also indicated associations, but these have not been replicated.…”
Section: After Gwasmentioning
confidence: 77%
“…In the case of Barrett oesophagus, tissue is accessible via upper endoscopy. To that end, whole and paired exomic sequencing of normal and Barrett oesophagus has unravelled a crucial role for mutations of TP53 and CDKN2A 124126 . Although the exact consequences of TP53 mutations in the development of Barrett oesophagus remain to be elucidated, it is possible that such mutations might serve as a gatekeeper for the maintenance of metaplasia and/or drive the conversion of metaplasia to low-grade dysplasia in the oesophagus 124 and perhaps the stomach as well 127 .…”
Section: Epigenetic and Genomic Considerationsmentioning
confidence: 99%
“…19 Research has now identified risk loci for Barrett's oesophagus associated carcinogenesis. [20][21][22][23] These findings could be used for research examining tailored prevention in individuals at high risk of OAC. There is presently limited scientific evidence supporting specific preventive measures in OAC, 24 but aspirin and antireflux therapy are being tested an RCT of patients with Barrett's oesophagus (AspECT).…”
Section: Adenocarcinomamentioning
confidence: 99%